HUBUNGAN MASA KERJA DAN LAMA KERJA DENGAN KADAR TIMBAL (Pb) DALAM DARAH PADA BAGIAN PENGECATAN, INDUSTRI KAROSERI SEMARANG - Pusparini, Diah Ayu; Setiani, Onny; Darundiati, Yusniar Hanani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Lead (Pb) is a toxic material, it can be accumulated in the body and it caused several health problems. The used of lead is widely used in industrial processes one of them in carooserie industry. Which wasin the painting body of a car industry, because The paint that used contains Pb. Long time duration of exposure a person is exposed to lead at work can increase the lead levels in blood so that it can reduce productivity in the work and caused high risk accident. This study aimed to analyze the association between long period of work and working timeof employment with high levels of lead (Pb) level in the blood of workers repainting parts body of car in carroserie industrial Semarang. Design of the researched was cross sectional with analytic observational research. the number of samples in this study was taken by purpossive random sampling. Data were collected through observation, interviews and laboratorytests. The level of lead in the blood of 34 respondents and measurement of air Pb. Univariate analysis, bivariate analysis was using Chi Square test. The results of the statistical test Chi Square showed the association of work period with Pb levels in the blood (p-value = 0.106) with 95 % CI (0,525- 1,110) and PR 0,764 and a long working association with Pb levels in the blood (p-value = 0,125) with 95 % CI (0,033– 0,284) and PR 0,097.It can be concluded that there was no significant association betweenwork period with lead levels of blood, and there was no association between working time of employment with lead levels in the blood on the worker of painting section, industrial carroserie Semarang